Development of Label for Coconut Juice, Klin Ai Tan Community Enterprise, Bang Thorat Sub-District, Mueang Samut Sakhon District, Samut Sakhon Province. - Sompoangeon, Saneh; Nudang, Sopa (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The objectives of this research work are 1) to study on information and direction for the development of label of coconut juice product of Klin Ai Tan Community Enterprise, Bang Thorat Sub-district, Mueang Samut Sakhon District, Samut Sakhon Province; 2) to develop label of coconut juice product; and 3) to assess the satisfaction toward the prototype label of coconut juice product. This research work uses mixed methodology that is the combination between qualitative and qualitative research methodologies. The area in which the research work is conducted is Bang Thorat Sub-district, Mueang Samut Sakhon District, Samut Sakhon Province. The key informants consist of 3 community enterprise members, 5 design experts and 100 samples who are consumers, making the total number of key informants become 108. The tools used on this research include the semi-structured interview script, the questionnaire of the evaluation of label of coconut juice product and the questionnaire of the assessment of satisfaction. The samples are selected with purposive sampling and random sampling techniques. The statistical values used include percentages, means and standard deviation. The findings from the research show as follows. 1) Klin Ai Tan Community Enterprise has been producing 100 percent coconut juice from the pollen of coconut flowers. The group has developed and added value to local raw material by transforming it. However, Klin Ai Tan Community Enterprise still lacks of knowledge and comprehension in marketing principles; additionally, there are still few channels for distribution and promotion of the product. Consequently, the product is not well known among consumers. Also, the current label of the product has no focal point to communicate to consumers. Thus. It cannot attract consumers. The direction for developing the label for coconut juice is to design the label to look outstanding with the key factor of creative economy approach and the key factor of graphic design. 2) In this project, 5 new labels of coconut juice product are designed. The design with the greatest mean is Design 2 which is appropriate in the high level (𝑥̅ = 3.69, S.D. = 0.98). Afterward, a prototype label in Design 2 is produced. 3) The findings from the assessment of samples’ satisfaction towards the designed label show that the samples are highly satisfied with the overall design of the label of coconut juice product (𝑥̅ = 4.08, S.D. = 0.95). Meanwhile, the factor with the highest mean is the factor of creative economy approach, which has achieved the high level of satisfaction (𝑥̅ = 4.13, S.D. = 0.92). As for the other factor, or the factor of the communication of the label, the satisfaction in high level (𝑥̅ = 4.03, S.D. = 0.97). The item in the factor of creative economy approach that consumers are most satisfied with is the item of the capability of the label of adding value to a new product that is made from local raw material, with the satisfaction in the high level (𝑥̅ = 4.19, S.D. = 0.87). As for the factor of the communication of the label, the consumers are most satisfied with the item of the capability of the image that clearly depicts the product and is beautiful, with all signs and symbols in proper sizes shown, the satisfaction to which is in the high level (𝑥̅ = 4.13, S.D. = 0.91).